State and future of the 'citadel' and of the heterodoxies in economics: challenges and dangers, convergences and cooperation - Wolfram Elsner (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This keynote reflects on the phased-out original neoclassical research program and the dominance of originally heterodox issues and questions, all beyond the 'optimality and equilibrium of the market economy', in modern cutting-edge economic research. This provides opportunities for heterodoxies and a number of severe internal consistency problems in the current mainstream – between their serious research in terms of complexity, dynamics, evolution, institutions and political economy, which they share with the different heterodoxies, and the ideological mantras they keep sticking to in mass teaching, textbooks, commercial research, policy advice and media statements. The severe financial and comprehensive crises have not only left the mainstream largely unswayed, but have rendered economics an even more contested area. The ideological function of the mainstream for the existing economic system seems to have become even more pronounced. On top of that, there is a comprehensive and fatal counterattack against a potential pluralism of ideas and theories and paradigmatic competition, put forward against the heterodoxies and for ideological cleansing of the discipline, spurred on in the disguise of ranking games. The conception and methodologies of the evaluation and ranking procedures have been proved to be fundamentally mistaken and flawed, but are nevertheless implemented against heterodox thinking worldwide. Examples are given throughout the note. Against this background, this keynote reflects about the status of the heterodoxies and current opportunities and ways to establish a relevant, real-world and useful economic discipline through cooperation and proactive pluralism.
Keywords: A1; A2; B0; B5; C0; 330; neoclassical economics; GET; evolutionary economics; institutional economics; post-Keynesian economics; complexity economics; real-world economics; heterodox economics; economic paradigms; economic teaching; pluralism; microfoundations of macro; macrofoundations of micro